Development of the RAKHMATTRIX Gamification Platform Based on the Mystery Object Challenge - Rakhmat Witdiyanto; Yayi Febdia Pradani; Marsono Marsono (Universitas Negeri Padang, 2026)
This study aimed to develop RAKHMATTRIX gamification media based on Mystery Object Challenge in Computer Aided Design (CAD) learning using the ADDIE development model. The research was conducted at SMK Muhammadiyah 1 Kepanjen for tenth-grade students in CAD learning. The developed media combines gamification elements, mystery box challenges, and blind design challenge activities to encourage students’ spatial visualization and creativity in creating 2D and 3D designs using Autodesk Inventor. The research stages consisted of analysis, design, development, implementation and evaluation. Data collection techniques included expert validation and students response questionnaires. Media validation was carried out by media experts and material experts to determine the RAKHMATTRIX gamification media obtained a very feasible category based on expert validation results. In addition, students responses indicated that the developed media was able to create a more interactive, interesting, and student-centered learning environment in CAD learning. Therefore, the RAKHMATTRIX gamification media is feasible to be used as a learning medium in CAD subjects.